Analisis Implementasi Etika Bisnis Terhadap Kinerja Perusahaan PT Goto Gojek Tokopedia Tbk - Memah, Ester; Rakinaung, Jesica; Rorong, Ananda Karunia; Hadinata, Graccio (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Business ethics form the moral foundation that guides corporate operations and stakeholder interactions, fostering trust, strengthening relationships, and promoting long-term business sustainability. In the digital industry, the application of business ethics has become increasingly critical due to the complexity of interactions among companies, partners, and customers. PT GoTo Gojek Tokopedia Tbk, established through the 2021 merger of Gojek and Tokopedia, faces substantial challenges in upholding ethical principles amid the dynamic landscape of Indonesia’s digital economy. This study adopts a descriptive qualitative approach, utilizing observation and literature review, to examine the extent to which the implementation of business ethics at GoTo contributes to its corporate performance. The findings indicate that consistent ethical practices significantly enhance corporate reputation, improve customer loyalty, and foster a healthy work environment. The integration of fairness, honesty, transparency, and social responsibility has proven to be critical in ensuring corporate sustainability and growth within the competitive digital industry. This study underscores the imperative for companies to systematically embed ethical principles into all operational activities in order to address evolving regulatory frameworks, market competition, and rising societal expectations.